CRIMINAL LIABILITY FOR ONLINE GAMBLING PROMOTION IN THE YOUTUBE COMMENT COLUMN - Hariri, Mochammad Sofyan; Guntara, Deny; Abas, Muhamad; Pratama, Raka Indra (Hukum Responsif, 2025)
The phenomenon of online gambling promotion through the YouTube comment column is a new challenge in criminal law enforcement in the digital era. Although it seems trivial, this action is part of a crime that can harm society. This study aims to analyze the existing online gambling regulations in Indonesia and the forms of criminal liability against perpetrators of online gambling promotion in YouTube comment sections. The method employed is a normative juridical approach with a legislative focus and a literature study. The results of the study show that the act of promoting online gambling in the comment column can be categorized as violating Article 27 paragraph (2) of the ITE Law and Article 303 of the Criminal Code (as well as the provisions of articles 426 and 427 in the New Criminal Code) because of deliberately disseminating electronic information containing gambling without permission.  Under certain conditions, YouTube account owners can also be held accountable if they neglect to moderate. Meanwhile, platforms like YouTube have a responsibility to take down illegal content. The results of this study indicate that online gambling promotion through comments can still be legally charged, even though it is done indirectly, suggesting that an adaptive and collaborative legal approach is necessary among authorities, platforms, and the public.